Transformasi Tampilan Produk UMKM melalui Pelatihan Desain Mock Up, Logo, dan Kemasan - Ari Kusmiatun; Arsianti Latifah; Denny Indria Ferawati; Eni Puji Astuti (GUYUB: Journal of Community Engagement, 2025)
The low level of understanding and skills among MSME actors in building product branding is one of the factors weakening business competitiveness, especially in terms of visual identity and packaging. This has the potential to hamper business continuity. This condition is experienced by the UPPKS Lestari Jaya group in Bantul, Yogyakarta, most of whose businesses do not yet have logos, packaging designs, or focused branding strategies, making it difficult for them to compete in a wider market. This community service program aims to improve the capacity of MSME players in designing products and services with selling value. The implementation methods include needs analysis, practice-based training, mentoring, and evaluation. The activity was attended by 20 business actors with business categories including processed foods, fashion products, and household services. The program results showed that all participants successfully produced branding outputs in the form of 20 business logos, product packaging designs, and visual identities that matched the characteristics of their respective businesses. The evaluation of the results showed an increase in the visual quality of the businesses in terms of brand identity clarity, design suitability, and visual appeal. This community service program has had an impact on improving the readiness of partner MSMEs to market their products and services more competitively and has become the basis for sustainable business development.